1994
DOI: 10.1002/cne.903500211
|View full text |Cite
|
Sign up to set email alerts
|

Two types of interneuron in the dorsal lateral geniculate nucleus of the rat: A combined NADPH diaphorase histochemical and GABA immunocytochemical study

Abstract: The rationale for this study was to provide a comprehensive light microscopical description of the morphology of diaphorase-reactive neurons and neuropil elements in the dorsal lateral geniculate nucleus (dLGN) of the rat. An additional objective was to quantitatively assess whether a subpopulation of the diaphorase-reactive neurons, previously shown to be GABA-immunoreactive, constitute a distinct type of local-circuit neuron in the rat dLGN. Diaphorase activity was localised in a population of predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 69 publications
4
37
0
Order By: Relevance
“…Outside the midline nuclei, the only thalamic site containing a relatively high number of neurons that express NOS was LG, a notable exception to the otherwise striking lack of positive cell bodies in the primary thalamic relay nuclei. The present data on the distribution of NADPH-d-positive neurons in LG are in agreement with previous studies in the adult rat (Mitrofanis, 1992;Vincent and Kimura, 1992;Gabbott and Bacon, 1994).…”
Section: Nos Is Discretely Localized In the Adult Thalamussupporting
confidence: 94%
See 1 more Smart Citation
“…Outside the midline nuclei, the only thalamic site containing a relatively high number of neurons that express NOS was LG, a notable exception to the otherwise striking lack of positive cell bodies in the primary thalamic relay nuclei. The present data on the distribution of NADPH-d-positive neurons in LG are in agreement with previous studies in the adult rat (Mitrofanis, 1992;Vincent and Kimura, 1992;Gabbott and Bacon, 1994).…”
Section: Nos Is Discretely Localized In the Adult Thalamussupporting
confidence: 94%
“…As for the thalamic cell types that were found in the present study to express NOS, it has been reported that a large proportion of NADPH-d-positive cell bodies in the rat DLG are GABA-immunoreactive and represent a subpopulation of interneurons (Mitrofanis, 1992;Gabbott and Bacon, 1994). In support of the concept that subsets of thalamic interneurons may express NOS, this enzyme has also been detected in a subpopulation of GABAergic cells in the cat VB (Meng et al, 1996).…”
Section: Nos Is Discretely Localized In the Adult Thalamussupporting
confidence: 69%
“…Recently several investigators have described the distribution of NOergic neurons in relation to aminergic neurons in different regions of the central nervous system, including the zona inserta 17) , prefrontal cortex 13) , medulla oblongata 21) , hippocampus 37) , cuneate nucleus 35) , olfactory bulb 1) , lateral geniculate nucleus 14) , spinal cord 31) , and cerebral cortex 36) . Nevertheless, little is known about the relationship between NO and neuroactive amino acids in the auditory nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the above approach has been used widely for mapping NOS-containing (presumably NOergic) neurons in the central nervous system 3,38) . NADPH-d histochemistry has also been combined with immunohistochemistry to assess relationships between the distribu-tion of NO and traditional neurotransmitters in various regions of the CNS 1,14,30,35,37) . Several studies suggest that NO and NOS play a role in audition.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopic data showed that these neurons were a source of GABAergic terminals within the ventrobasal nucleus (Meng et al, 1997). Similarly, a subset of interneurons in the rat LGN have been identified using by using nicotinadamine phosphate (NADPH)-diaphorase histochemistry to stain for BNOS (Gabbot and Bacon, 1994).…”
mentioning
confidence: 99%